Exploring healthcare workers’ intentions to volunteer in digital healthcare services for underserved communities: An extended TAM-based study - Almokdad, Eeman; Mouloudj, Kamel; Njoku, Anuli; Bouarar, Ahmed; Evans, Marian; Asanza, Dachel; Mouloudj, Smail (Electronic Journal of General Medicine, 2026)
Underserved communities face persistent challenges due to limited access to healthcare services. Digital volunteering offers opportunities for healthcare professionals to support these populations remotely. This study examined factors associated with healthcare workers’ intentions to participate in digital healthcare volunteering in Algeria. An extended technology acceptance model was used, incorporating perceived organizational support (OS), altruism, and social responsibility. A convenience sample of 142 healthcare workers completed a survey, and hierarchical regression analysis was conducted. Results indicated that perceived ease of use, social responsibility, altruism, perceived OS, and perceived usefulness were each significantly associated with intentions to engage in digital volunteering. The extended model explained 75.6% of the variance in intention, highlighting the relevance of psychological, organizational, and ethical factors. These findings provide insights for policymakers, healthcare organizations, and developers seeking to support digital volunteering initiatives. Limitations include the cross-sectional design and the use of convenience sampling, which may affect generalizability. Future research should consider longitudinal designs, larger and more diverse samples, and cross-cultural comparisons to validate and extend these findings.
Keywords: Affect (linguistics); Algeria; Digital health; Health care; Health professionals; Multilevel model; Relevance (law); Technology acceptance model; Variance (accounting); altruism; dept.pch; digital health; health disparities; health equity; healthcare access; organizational support; social marketing; social responsibility; telemedicine